2011
DOI: 10.1155/2011/627195
|View full text |Cite
|
Sign up to set email alerts
|

Spirooxazine Photoisomerization and Relaxation in Polymer Matrices

Abstract: 9′-Hydroxy-1,3,3-trimethylspiro[indoline-2,3′[3H]naphtha[2,1-b]-1,4oxazine] (SPO-7OH) was used in studies of photochromic transformations in polymer matrices. Illumination with UV lamp caused opening the spirostructure of the oxazine with formation of open merocyanine species absorbing at ca. 610 nm. The kinetic studies of thermal relaxation of the open form showed that this process can be described with a biexponential function including both photochemical reaction and rheological behaviour of the polymeric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A large dipole moment increases interactions of the dye molecule with the surrounding matrix and hence affects dye kinetics. Larkowska et al [21] observed that the relaxation reaction appeared to be slower when the dipolar interactions were more pronounced. Therefore, the large dipole moment of the spirooxazine dye molecules and their consequent higher polarity during isomerization may influence their behavior in relation to the matrix more compared to RR prints.…”
Section: Resultsmentioning
confidence: 99%
“…A large dipole moment increases interactions of the dye molecule with the surrounding matrix and hence affects dye kinetics. Larkowska et al [21] observed that the relaxation reaction appeared to be slower when the dipolar interactions were more pronounced. Therefore, the large dipole moment of the spirooxazine dye molecules and their consequent higher polarity during isomerization may influence their behavior in relation to the matrix more compared to RR prints.…”
Section: Resultsmentioning
confidence: 99%
“…Self-reporting materials are capable of showing a measurable, often visible indication of the conditions they have been subjected to. Spiropyrans are molecular switches that undergo a reversible molecular transformation to a merocyanine (MC) form in response to different stimuli such as mechanical stress, light, and heat and thereby showing a color change. , As the intensity of the color is linked to the amount of active molecules present, spiropyran should be an ideal self-reporting material. , Several self-assembly, self-reporting materials and optical sensors based on spiropyran have been successfully produced. In most of such systems, the spiropyran is either covalently linked to a polymer chain, or grafted on metallic surfaces. Most known systems of spiropyran as a mechanical stress indicator require its covalent incorporation into the main chain or as cross-links of the polymer. This results in long synthesis routes from commercially available starting materials to the final product, thus complicating the scale-up process. , There have been examples of studies on the mechanical sensitivity of spiropyran derivatives in crystal form, illustrating mechanochromic switching under high hydro static pressure. This implies that spiropyran can be used as an additive in the polymer composite system and would provide a more cost-effective solution. Photoinduced mechanical switching of spiropyran in a composite system has been demonstrated in poly­(ethyl methacrylate- co -methyl acrylate) (PEMMA) films . These films were produced by blending 3 wt % of spiropyran, and the stiffness of the material was altered by the photoinduced switching.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different photochromic dyes, spirooxazine have been extensively investigated due to their high fatigue resistance [9,10].Spirooxazine reversible photo transformation mechanism involves photochemical process of ring opening of spirocompound yielding merocyanines and thermal or photochemical relaxation process of merocyanines closing ring [11]. The process of reversible isomerization is present in figure 1.…”
Section: Introductionmentioning
confidence: 99%